Analisis Strategi Marketing Digital Pada Bumdes Lestari Jaya Desa Sindang Jaya Kabupaten Rejang Lebong - Siti Hanilla; Andriyani Prawitasari; Sri Handayani (UNIVED Press, 2022)
This research is to analyze the use of digital marketing strategies implemented at BUMDes Lestari Jaya and analyze the factors that hinder the development of BUMDes Lestari Jaya online stores and analyze the proposed appropriate marketing strategies to optimize the reach of BUMDes Lastari Jaya Digital Marketing. This analysis process is carried out on Digital Marketing activities that have been carried out by BUMDes Lestari jaya using SWOT Analysis. Data This research was obtained from the results of several previous studies, interview results and questionnaire results distributed to 60 respondents consisting of Consumers and Social Media Folowers of BUMdes Lestari Jaya as a source of information for improving the digital Marketing Strategy of BUMDes Lestari Jaya. From the results of the SWOT analysis obtained : Strenght : a. It has abundant raw materials, b. The quality of the poduk is quite good, c. There are several variants of palm sugar products as an option for consumers, d.Dapay receives orders in large quantities, e.The potential of partners as reselers is very large. Weakness: a. Digital Marketing Strategy is not yet on Target, b. In managing the Digital Marketing Strategy has not been professional and consistent, c. Opportunities for resellers have not been opened, d. Limited human resources in managing social media as promotional advice. Opportunity: a.The scope of the Digital Market is very wide, b.The opportunity for cooperation with resellers is still very wide open, c.The need for brown sugar is very much. Threts : a.Fierce competition with similar products, b.Price competition with products from other regions